The use of jackfruit peel as filler in polylactic acid biocomposite films: effect of filler modification - Santhi Dewi A/P Perumal (School of Metallurgy Engineering, University Malaysia Perlis, 2016)
The biocomposite films of jackfruit peel filler (JPF) and poly(lactic acid) (PLA) were prepared by solution casting method. The effect of jackfruit peel filler (JPF) content and modification of JPF by silane coupling agent on tensile and thermal properties, morphology and biodegradation of PLA/JPF biocomposite films were studied.